2009
DOI: 10.1016/s0034-7094(09)70097-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Local Anesthetics on the Neuromuscular Blockade Produced by Rocuronium. Effects of Lidocaine and 50% Enantiomeric Excess Bupivacaine on the Neuromuscular Junction

Abstract: Local anesthetics caused a potentiation of the neuromuscular blockade produced by rocuronium. The results showed pre- and post-synaptic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
2
12
1
5
Order By: Relevance
“…In electrophysiological studies, similarly to other studies [4][5]22 , we observed that local anesthetics did not produce . The study of MEPPs is important to investigate the presynaptic effects of the drugs used, due to its interference in mediator release 22 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In electrophysiological studies, similarly to other studies [4][5]22 , we observed that local anesthetics did not produce . The study of MEPPs is important to investigate the presynaptic effects of the drugs used, due to its interference in mediator release 22 .…”
Section: Discussionsupporting
confidence: 90%
“…The study of MEPPs is important to investigate the presynaptic effects of the drugs used, due to its interference in mediator release 22 . In contrast to previous reports on lidocaine [4][5]21 , describing that it initially increases MEPP frequency, the local anesthetics used in the study caused a progressive decrease both in the frequency and amplitude of these potentials until complete blockade.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…neuromuscular blockers more indicated for rapid sequence intubation are succinylcholine and rocuronium due to their lower latency 26 . the interaction between local anesthetics and neuromuscular blockers is known and demonstrated in different models 19,23,24,39,40 . local anesthetics have a strong capability of inhibiting several subtypes of nicotinic receptors of acetylcholine, including muscular 22,[41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…the interaction of local anesthetics with preand post-synaptic nicotinic receptors in the neuromuscular junction explains this phenomenon [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%